Prevention and Treatment of Epitheliopathy as a Result of Acute Inflammatory Diseases of the Ocular Surface - E. A. Drozdova; E. V. Berdnikova (Oftalʹmologiâ, 2023)
Acute inflammatory diseases of the ocular surface occur in case of epitheliopathy. As a result, most patients complain of discomfort and persistence of residual inflammation after the infection has been stopped.The purpose: to assess the degree of damage to the ocular surface as a result of bacterial conjunctivitis and keratitis, as well as the regenerative effect of dexpanthenol 5 % eye gel on the healing and restoration of the functional activity of the ocular surface epithelium.Methods. A non-randomized case-control study was performed in patients with a bacterial infection of the conjunctiva and cornea. Under supervision there were 23 patients (46 eyes) diagnosed with bacterial conjunctivitis and 31 patients (31 eyes) with bacterial keratitis. According to the study design, patients were divided into two groups. After stopping the acute process, dexpanthenol 5 % eye gel was prescribed. To control the effectiveness, the tear film rupture time, the degree of damage to the mucin coating and surface epithelial cells were evaluated. Diagnostic tests with vital dyes (fluorescein (FA) and lyssamine green (LG)) were performed before the appointment of the gel, then seven and thirty days after the appointment of the drug.Results. After the relief of bacterial inflammation, 86.9 % patients with conjunctivitis and in all cases of keratitis had complaints (unpleasant sensations and redness of the eyes, blurred vision). There was a decrease in tear break-up time (TBUT) test, a significant accumulation of dye in the conjunctiva in both study groups and a partial accumulation of FA in the cornea, more intense in keratitis. After 7 days Corneregel use, there was an increase in TBUT compared to the baseline level, with a further increase in this indicator after a 1 month, a decrease in the manifestation of conjunctival epitheliopathy and the degree of corneal staining.Conclusions. The appointment of dexpanthenol 5 % eye gel after stopping a bacterial infection helps to relieve discomfort, accelerates the restoration of regeneration of the epithelial cells of the ocular surface, and increases the strength of the tear film.